Navigating a Way Forward: How Women Survivors of Breast Cancer and Their Partners Face Challenges Adapting to Their Changed Lives - Keesing, Sharon Lee (Curtin University, 2018)
Many women survivors of breast cancer and their partners experience challenges while attempting to resume meaningful activities and important life roles following treatment cessation. This mixed method study aimed to explore these challenges and appraise the current services available to meet ongoing needs. Three major themes were determined; women and partners experience occupational disruption, use of a survivorship care plan and rehabilitation is warranted, occupational therapy has a role in assisting women and partners during survivorship.